Human papillomavirus infection and risk factors to cervical cancer in asymptomatic women in the region of the Northeast of Brazil - Farias, Karol Fireman de; Silva, Adrielle Sonara Gomes; Santos, Ana Caroline Melo dos; Silva, Adriely Ferreira da; Silva, Denise Macedo da; Moura, Edilson Leite de; Araújo, Alexandre Wendel de Moura; Nascimento, Cristiane Araújo; Martins, Danyelly Bruneska Gondim; Figueiredo, Elaine Virginia Martins de Souza; Filho, José Luiz de Lima (Journal of Health & Biological Sciences, 2021)
Objective: This study sought to identify the presence of HPV infection and the risk factors related to susceptibility to cervical cancer in asymptomatic women. Methods: It is a cross-sectional study with 428 users attended Basic Health Units, in Arapiraca, Alagoas, Brazil. Sociodemographic, behavioral variables, and cytopathological reports were collected. Molecular detection of the HPV virus was performed by Nested-PCR. Statistical analysis was conducted with SPSS version 22.0. Results: A total of 428 women were studied, HPV DNA detected in 39.2% (n = 168), with a mean age of 41 years old. There was an association of HPV with use of oral contraceptives (p <0.016) and alcoholism (p <0.038). It was showed a higher frequency of positive HPV in women older than 25 years old (88.7%), up to 5 sexual partners (93.4%), up to 3 pregnancies (71.4%), and with the cytopathologic results within the limits of normality (61.9%). HPV was identified in 40.3% (104/258) of the women with results within the limits of normality. Conclusion: Our results suggest that the use of oral contraceptives and alcoholism may be considered as possible risk factors related to cervical oncogenesis. With this, it is necessary to propose interventions aimed at the health education of this population, actions of prevention, and early detection.